Awareness, knowledge and attitude toward orthostatic hypotension among elderlies - Ch’ng, Hui Kee (2022)
Orthostatic hypotension (OH) is a drop in blood pressure during the motion of changing posture from laying down position to upright position. Studies shows that the prevalence of orthostatic hypotension is high and is a commonly associated with old age. Few medications also may contribute to (OH). (OH) may be associated with non-willingness to move out of bed to social isolation. It may lead to fall and associated head injury and death. Hence, the awareness & knowledge of (OH) needs further attention. The aim of the study is to determine the level of awareness, knowledge, and attitude toward (OH) among academic and non-academic staff. This study was conducted on academic and non-academic population in a University in Malaysia. Self-prepared and validated questionnaire have been used for this survey. This questionnaire had 4 sections (demographic data, awareness, knowledge of (OH) & attitude towards (OH) A survey is carried out via online and printed version questionnaire. Mann- Whitney U test and Spearman’s Rank- Order correlation test to identify the level of awareness, knowledge, and attitude toward orthostatic hypotension among UTAR academic and non-academic staff using SPSS version 26. A total of 203 participants is recruited, but only a total of 195 respondents were processed. 8 participants are filtered due to incomplete questionnaire and disagreement on consent form. The respondents contain 44.6% of academic staff and 55.4% of non-academic staff. There is a fair level of awareness is observed but high level of knowledge and good attitude is observed; Awareness, MS= 33.6  16.3 Knowledge, MS= 73.4  8.5, Attitude, MS= 86.3  14.1. There is no statistically significant difference between academic and nonacademic staff on level of awareness, knowledge, and attitude (Awareness, p=0.645, Knowledge, p= 0.153, Attitude, p=0.258). There is a significant relationship between level of awareness and attitude among staff (p< 0.001). There is no significant relationship between level of knowledge and attitude among staff (p= 0.073). This study shows high level of knowledge and good attitude towards (OH) is performed among UTAR staff. However, further efforts should be made to increase the awareness. Future study is needed to fulfil the gap knowledge and insufficiency information regarding orthostatic hypotension. By fulfilling the physiotherapy could play an important role in prevention and management of (OH), & scope of physiotherapy needs further studies in this area.